2011
DOI: 10.1007/s00167-011-1434-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of kinematics and range of motion in high-flexion total knee arthroplasty: cruciate retaining vs. substituting designs

Abstract: PS high-flexion TKA provided greater weight-bearing maximal flexion and posterior femoral roll-back than CR high-flexion TKA, although no difference in clinical outcomes was observed between the two prosthesis designs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 26 publications
5
50
0
1
Order By: Relevance
“…Traditionally, it is recognised that the PS prosthesis and procedure will result in a different knee condition, including postoperative kinematics and outcomes, compared with CR [22][23][24][25]. In our study, joint-component gap at flexion was significantly larger than at extension in PS using the measured-resection technique.…”
Section: Discussionmentioning
confidence: 47%
“…Traditionally, it is recognised that the PS prosthesis and procedure will result in a different knee condition, including postoperative kinematics and outcomes, compared with CR [22][23][24][25]. In our study, joint-component gap at flexion was significantly larger than at extension in PS using the measured-resection technique.…”
Section: Discussionmentioning
confidence: 47%
“…Second, the uniform use of one HF fixed-bearing prosthesis by a single surgeon suggests our findings might not be generalizable to low-volume surgeons or those using other HF prostheses such as cruciateretaining or mobile-bearing designs. Third, although the high proportion of females in our cohort is typical of Korean patients undergoing TKA [5,20,25,26,41], this also reduces the extent to which our results can be generalized. Fourth, the followup period of 4.7 years (range, 2-8 years) will not likely reflect the ultimate incidence of prosthesis-related loosening because it will almost certainly increase during further followup of our cohort, although 63% of early aseptic loosening requiring revision occurred within 2 years of followup in another study [36].…”
Section: Discussionmentioning
confidence: 90%
“…Early aseptic loosening of the femoral component reportedly occurs in 0% to 0.9% of patients at 2 to 10 years [4,10,27,29,44,48] in conventional TKA, and concerns have therefore been raised about the high incidence of early aseptic loosening in HF designs [7,17]. However, a number of clinical studies reporting 25 to 259 knees [3,8,20,[24][25][26] have suggested conflicting findings with only a few instances of prosthesis-related failures after HF TKA at mean followups of 12 to 51 months even in the same ethnic group [5,20,[24][25][26]41]. The risk of early aseptic loosening after HF TKA in large cohort studies is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al [11] in 2009, in a prospective randomized study (minimum follow-up of 2 years), compared high-flexion posteriorretained with high-flexion posterior-stabilized prosthesis and also did not notice a difference in range of knee motion, clinical and radiographic results. However, in 2011, Seon et al [12] published another prospective randomized study which also compared high-flexion posterior-stabilized TKA with high-flexion posterior-retained TKA and disagreed: the former prosthesis proved superior to the latter in weight-bearing maximum flexion and posterior femoral roll-back, although no difference was noted in clinical outcomes. Yagishita et al [13] performed a prospective randomized study in 2012, with a minimum followup of 5 years, which indicated that posterior-stabilized prosthesis showed better results in postoperative knee motion, posterior knee pain at passive flexion and patient satisfaction, but no significant difference was found between the 2 types of TKA regarding Knee Society Score.…”
Section: Retaining Tkamentioning
confidence: 99%
“…Yagishita et al [13] Prospective, randomized study comparing high-flexion CR design implanted in one knee and high-flexion PS design implanted in the other knee in simultaneous bilateral TKA PS prosthesis better in postoperative knee motion, posterior knee pain at passive flexion and patient satisfaction Seon et al [12] Prospective randomized trial, comparing in vivo kinematics, range of motion, and functional outcomes in patients who received either a highflexion cruciate retaining or a high-flexion cruciate substituting TKR No differences in clinical outcomes. PS TKR superior to CR TKR in weight-bearing maximum flexion and posterior femoral roll-back Kim et al [11] Prospective randomized trial, comparing ROM and functional outcome in knees receiving either a high-flexion posterior cruciate-retaining or a highflexion posterior cruciate-substituting TKR…”
Section: No Differences Between the 2 Designsmentioning
confidence: 99%